Fabrication of Substituted-Hydroxyapatite/Poly(vinyl pyrrolidone)-Poly(methyl methacrylate) Biocomposites for Bone Tissue Engineering Applications - Priya, G.; Vijayakumari, N. (Asian Journal of Chemistry, 2021)
Present work based on the development and incorporation of zinc-cerium substituted hydroxyapatite (ZCHA) nanoparticles into the host material of the dual polymer blend of poly(vinyl pyrrolidone) (PVD)-poly(methyl methacrylate) (PMMA). Numerous characterization techniques such as FTIR, XRD and SEM-EDX have been used in morphological and structural investigations of prepared nanoparticles and ZCHA reinforced PMMA-PVD biocomposites. The mechanical properties of ZCHA/PVD-PMMA biocomposites, like compressive strength was evaluated. To examine the biocompatibility of biocomposites, hemocompatibility experiments have been carried out. The antimicrobial activities of biocomposites toward Gram-positive and Gram-negative bacteria have also been tested and the cytotoxic existence of biocomposites has been evaluated using the MTT assay experiment. The developed ZCHA/PVD-PMMA biocomposites is suggested to provide the finest medicinal benefits in the application of biomaterials.